Demonstration-based help for interactive systems - Rodrigues, Pedro Miguel Freitas (2018)
The usability of day-to-day applications is of utmost importance. The lack of usability of these is one of the causes of frustration at work, as it creates barriers to the execution of tasks. The Change of applications by third parties, to increase usability, is difficult because it requires, usually, access to source codes and an increase on its complexity. This work proposes and implements a demonstration help tool that allows the improvement of tasks completion, decreases the time spent, and reduces the cost of learning. An analysis of work on aid tools is presented identifying positive aspects and research opportunities. The help tool developed allows the creation of automation through picture-driven computing, which makes it possible to develop help mechanisms independent from application source codes. Since the tool is image oriented, and tasks can involve multiple applications, it is also possible to develop help scripts that are not restricted to just one application. User studies were done with the objectives of validating the work developed and identifying platforms and tasks with usability problems in the business world. It was concluded that the work has positive effects in the accomplishment of tasks.